An efficient delivery of photosensitizers and hypoxic prodrugs for a tumor combination therapy by membrane camouflage nanoparticles. Issue 14 (19th March 2020) - Wang, Hanjie; Zhang, Chaonan; Zhang, Yingying; Tian, Ran; Cheng, Guohui; Pan, Huizhuo; Cui, Meihui; Chang, Jin
Abstract : Photodynamic therapy (PDT) is an oxygen-dependent, non-invasive cancer treatment. Abstract : Photodynamic therapy (PDT) is an oxygen-dependent, non-invasive cancer treatment. The hypoxia in the tumor environment limits the therapeutic effects of PDT. The combined delivery of photosensitizers and hypoxic prodrugs is expected to improve the efficacy of tumor treatment. In this paper, an erythrocyte and tumor cell membrane camouflage nanocarrier co-loaded with a photosensitizer (indocyanine green) and a hypoxic prodrug (tirapazamine) were used to combine PDT with chemotherapy. The system achieved less macrophage clearance through erythrocyte membranes and tumor-targeted tumor cell membranes, thereby inducing cell death and increasing tumor environment hypoxia by NIR irradiation of photosensitizers. Furthermore, the hypoxic environment activated TPZ to kill more tumor cells. In vivo results showed that the tumor inhibition rate of the drug-loaded nanoparticles increased from 34% to 64% after membrane modification. Moreover, the tumor inhibition rate of the photodynamic treatment group alone was only 47%, and the tumor inhibition rate after the combination was 1.3 times that of photodynamic therapy alone. Our platform is expected to contribute to the further application of cancer combination therapy.